Dietary assessment in the 1993 Pelotas (Brazil) birth cohort study: comparing energy intake with energy expenditure Avaliação dietética da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993: uma comparação da ingestão e do gasto de energia - Denise P. Gigante; Felipe Fossati Reichert; Pedro C. Hallal; Rosângela Velleda de Souza; Marilda Borges Neutzling; Maria de Fátima Alves Vieira; Maria Cecilia Formoso Assunção; Cora Luiza Araújo; Ana M. B. Menezes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The study aims to describe and compare two methods of energy intake assessment and one measure of energy expenditure applied in adolescents from a birth cohort. In a sub-sample of the 1993 Pelotas (Brazil) birth cohort, followed up in 2006-7, information on intake was obtained through a food-frequency questionnaire (FFQ) and three 24-hour-recalls (24hR), while energy expenditure was assessed using an accelerometer. Bland & Altman plots were used in the analyses in order to compare the methods. The mean difference between FFQ and 24hR was 592 ± 929cal/day. Compared to energy expenditure, intake was overestimated when measured by FFQ (357 ± 968cal/day) and underestimated by 24hR (-278 ± 714cal/day). In spite of the great differences between energy intake obtained using the two methods, lower differences were observed when these methods were compared to expenditure. O objetivo do estudo foi descrever e comparar dois métodos de avaliação de consumo calórico e uma medida de gasto energético aplicados em adolescentes de uma coorte de nascimentos. Em uma subamostra da coorte de 1993 de Pelotas, Rio Grande do Sul, Brasil, acompanhada em 2006-2007, informações sobre consumo calórico foram obtidas através de questionário de frequência alimentar (QFA) e três recordatórios de 24 horas (R24h), enquanto gasto energético foi avaliado por acelerômetro. Gráficos de Bland & Altman foram usados na comparação dos métodos. A diferença média entre QFA e R24h foi 592 ± 929cal/dia. Ao comparar com gasto energético, o consumo foi superestimado se medido pelo QFA (357 ± 968cal/dia) e subestimado pelo R24h (-278 ± 714cal/dia). Apesar da grande diferença no consumo, menores diferenças foram observadas quando os dois métodos foram comparados ao gasto energético.